ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP ANAK YANG DIJADIKAN KURIR NARKOTIKA - Maryani Melindawati; Madiasa Ablisar; Mahmud Mulyadi; Edi Ikhsan (USU LAW JOURNAL, 2018)
ABSTRACT Narcotics abuse seems a natural thing in Indonesia. It appears in news on criminality program every day. It is illegal which means that if one does not have license or authority to use narcotics, either for himself or for other people, it can be categorized as narcotics abuse. A child who plays his role as a courier in drug trafficking can be called a child that is in conflict with law or juvenile delinquency. As young generation that functions as human resources for the national development, they need to be protected through strategic stages, either legally or educationally, and other related fields. The problem is that, in practice,  legal protection tends to punish them, instead of improving and bringing them back to their own good and honest nature. It is recommended that legislative body establish regulations on child criminal (as a courier in drug trafficking) so that it is not necessary to apply regulation for an adult as if the child is able to commit the crime as an adult. The regulation on diversion for all criminals, including children as couriers in drug trafficking and the limitation of diversion is only when they are sentenced to death should be changed. Law enforcers, aided by the government, should help realize any efforts which haven explained in Chapter IV, sub b of this research.   Keywords: Child, Narcotics, Legal Protection